2018
DOI: 10.1016/j.pbb.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Menthol facilitates dopamine-releasing effect of nicotine in rat nucleus accumbens

Abstract: Menthol is a significant flavoring additive in tobacco products. Accumulating clinical evidence suggests that menthol may promote tobacco smoking and nicotine dependence. Our previous studies demonstrated that menthol enhanced nicotine reinforcement in rats. However, it is unclear whether menthol interacts with nicotine at the neurochemical level. The present study used intracranial microdialysis to examine whether and the ways in which menthol affects nicotine-induced dopamine release in rats in the nucleus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Menthol is the most prominent flavor for tobacco products and was considered to be an inert flavor additive, yet, studies have shown that menthol enhances nicotine reward-related and reinforcement-related behaviors in rodents ( Wang et al, 2014 ; Biswas et al, 2016 ; Henderson et al, 2017 ). The menthol-induced enhancement is because of a combination of effects on nicotinic acetylcholine receptor (nAChR) upregulation ( Brody et al, 2013 ; Henderson et al, 2016 , 2017 ), dopamine neuron excitability ( Henderson et al, 2018 ), dopamine release ( Zhang et al, 2018 ), and TrpM8-dependent mechanisms ( Fan et al, 2016 ). In addition to menthol, similar investigations into other popular ENDS flavors are being conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Menthol is the most prominent flavor for tobacco products and was considered to be an inert flavor additive, yet, studies have shown that menthol enhances nicotine reward-related and reinforcement-related behaviors in rodents ( Wang et al, 2014 ; Biswas et al, 2016 ; Henderson et al, 2017 ). The menthol-induced enhancement is because of a combination of effects on nicotinic acetylcholine receptor (nAChR) upregulation ( Brody et al, 2013 ; Henderson et al, 2016 , 2017 ), dopamine neuron excitability ( Henderson et al, 2018 ), dopamine release ( Zhang et al, 2018 ), and TrpM8-dependent mechanisms ( Fan et al, 2016 ). In addition to menthol, similar investigations into other popular ENDS flavors are being conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the inhibition of dopamine receptor D3 signaling in DC increases antigen cross-presentation [ 33 ], dopamine-dependent behavioral effects of nicotine were also documented [ 34 ]. As nicotine treatment inhibits proteasomal activities [ 12 ] and increased dopamine release [ 35 ], the phenomena that WT-Ub fails to restore the ubiquitination-induced effects might be due to nicotine-increased dopamine release and the potential role of dopamine receptor D3 signaling in DC cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the direct effects of menthol on nAChRs have begun to be identified. Menthol enhances the nicotine-induced upregulation of nAChRs [ 19 , 20 ] and enhances reward-related behavior in conditioned place preference assays [ 19 ], the vapor self-administration of nicotine [ 21 ], intravenous self-administration of nicotine [ 16 , 22 ], and nucleus accumbens dopamine release [ 23 ]. These findings support the previous findings that menthol may be a cue-reinforcer for nicotine use [ 24 ].…”
Section: Introductionmentioning
confidence: 99%